PENGELOLAAN MANAJEMEN KEUANGAN YANG PROFESIONAL DALAM PENGEMBANGAN BISNIS PADA ERA DIGITALISASI DI KELURAHAN DURIAN, KECAMATAN MEDAN TIMUR - Winata, Clarrissa; Salim, Denny; Sitompul, Pretty Naomi; Khairani, Khairani (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The purpose of this community service activity (PkM) is to provide knowledge and information on how to manage finances effectively so that it can be applied in the businesses of the community in Kelurahan Durian, Medan Timur District. The business owners in Kelurahan Durian, Medan Timur District can understand and comprehend how to manage financial management properly. Furthermore, the business owners in Kelurahan Durian, Medan Timur District will be able to learn about how to manage finances in business effectively in the era of digitalization. Overall, the PkM activities received a positive and enthusiastic response from the residents. Continued assistance will be provided to the business owners in Kelurahan Durian, Medan Timur District to enhance their skills and understanding of financial management in business during the digitalization era.